Chronic Exposure to Cigarette Smoke Affects the Ileum and Colon of Guinea Pigs Differently. Relaxin (RLX-2, Serelaxin) Prevents Most Local Damage - Traini, Chiara; Nistri, Silvia; Calosi, Laura; Vannucchi, Maria Giuliana (Frontiers in Pharmacology, 2022)
Cigarette smoking (CS) is the cause of several organ and apparatus diseases. The effects of smoke in the gut are partially known. Accumulating evidence has shown a relationship between smoking and inflammatory bowel disease, prompting us to investigate the mechanisms of action of smoking in animal models. Despite the role played by neuropeptides in gut inflammation, there are no reports on their role in animal models of smoking exposure. The hormone relaxin has shown anti-inflammatory properties in the intestine, and it might represent a putative therapy to prevent gut damage caused by smoking. Presently, we investigate the effects of chronic smoke exposure on inflammation, mucosal secretion, and vasoactive intestinal peptide (VIP) and substance P (SP) expressions in the ileum and colon of guinea pigs. We also verify the ability of relaxin to counter the smoke-induced effects. Smoke impacted plasma carbon monoxide (CO). In the ileum, it induced inflammatory infiltrates, fibrosis, and acidic mucin production; reduced the blood vessel area; decreased c-kit-positive mast cells and VIP-positive neurons; and increased the SP-positive nerve fibers. In the colon, it reduced the blood vessel area and the goblet cell area and decreased c-kit-positive mast cells, VIP-positive neurons, and SP-positive nerve fibers. Relaxin prevented most of the smoking-induced changes in the ileum, while it was less effective in the colon. This study shows the diverse sensitivity to CS between the ileum and the colon and demonstrates that both VIP and SP are affected by smoking. The efficacy of relaxin proposes this hormone as a potential anti-inflammatory therapeutic to counteract gut damage in humans affected by inflammatory bowel diseases.